PERAN PONDOK PESANTREN HIDAYATUTH THOLIBIN DALAM PENINGKATAN PENDIDIKAN AGAMA ISLAM PADA MASYARAKAT DAWUHAN MALANG - M Yusuf Alfan Khoirudin; Mohammad Afifulloh (Vicratina : Jurnal Ilmiah Keagamaan, 2021)
Islamic boarding schools have an important role in the order of life in society. Seeing before there was a pesantren, the Dawuhan community was very layman in understanding religious knowledge and disobedience everywhere, it was like a normal thing. Boarding school provides positive changes to improve and fix the wrong order of life. In the implementation of the Hidayatuth Tholibin Islamic Boarding School activity program, it has succeeded in fostering students, and the community is enthusiastic about participating in the religious education learning program. Such as madrasah diniyah programs and general ta'lim assemblies. The supporting factor for the implementation of the Hidayatuth Tholibin Islamic Boarding School activity program in improving Islamic religious education in the Dawuhan Malang community is good cooperation and high concern from various parties such as: guardians of students, students, alumni, community, and muhibin. Based on the results of research that has been carried out by researchers regarding the role of the Hidayatuth Tholibin Islamic Boarding School in improving Islamic religious education in the Dawuhan Malang community, namely the role or activities carried out by the Hidayatuth Tholibin Islamic Boarding School in accordance with what is expected in an institution and developments in the Dawuhan Malang community, namely by establish a ta'lim assembly. Other activities are establishing recitations and also organizing social activities. And most importantly, the Hidayatuth Tholibin Islamic Boarding School has played a role in educating morals, fortifying themselves from negative influences, and instilling religious values. This study uses a qualitative approach and the type of research used is descriptive analysis. Data collection is done by observation, interviews, and documents. To analyze the selected data using qualitative analysis from Miles and Huberman, namely through data reduction, data presentation, and drawing conclusions.